First molecular and morphometric data for the genus Allmania (Amaranthaceae), with the description of a new species from India - Sindhu, Arya; Iamonico, Duilio; Suresh, Veerankutty; Kumar, Venugopalan Nair Saradhamma Anil (Phytotaxa, 2022)
First molecular and morphometric investigations for the genus Allmania are presented. A new species of Allmania from the granite hillocks of Palakkad district (Kerala state, India), is described as A. multiflora. It differs from A. nodiflora by shape and length of tepals, diameter of the gynoecium, diameter and hairiness of seeds, length of bracts, length and hairiness of peduncles, number of flowers per synflorescence, colour of stigma, and occurrence of setae associated with the aril. Furthermore, sequence analysis of chloroplast genes (rbcL and matK) also support the distinctness of the new taxon. Original illustrations, photographs, and ecological data are also provided, as well as an evaluation of the conservation status.